A brief survey on multispectral iris recognition. (2016) - Roy, Kaushik; Shelton, Joseph; Esterline, Albert
In this survey, we report the current state of the art of multispectral iris recognition methods. We discuss the existing multispectral iris recognition schemes in the contexts of image acquisition, iris segmentation, texture analysis, matching, and performance evaluation. Other important research includes experimental evaluations, image databases, applications and systems, spectral ranges, and multispectral fusion that may affect the multispectral iris recognition.